Turistične destinacijske organizacije: Gonila povezanega kreativnega zelenega razvoja in trženja (University of Maribor Press, 2023)
Tourism Destination Organizations: Drivers of Connected Creative Green Development and Marketing. The monograph entitled ’TOURISM DESTINATION ORGANIZATIONS: drivers of connected creative green development and marketing’ consists of four scientific thematic sections for tourism employees in the public and private sectors, tourism and hospitality students and civil society representatives. In the discourses, 40 authors focused on: (i) sustainable management of tourist destinations, providers and experiences through the local added value, based on security in tourism and planned crisis management; (ii) digitization in tourism for the management and marketing of related stakeholder destinations; (iii) elements of destinations through: creative offer in nature, cultural heritage, architectural uniqueness, gastronomic tourism, accommodation on tourist farms, the role of incoming tourist agencies and tourist guides for unforgettable experiences; and (iv) the main products of Slovenian tourism: active tourism in nature; valorization of cultural heritage; wellness and health services; events and business meetings; gastronomic experiences and wine destinations. The studied contents can be an excellent guide for a clear positioning of Slovenian tourist destinations on the highly competitive green tourist map of Europe.